Exercise intervention lowers aberrant serum WISP-1 levels with insulin resistance in breast cancer survivors: a randomized controlled trial - Chang, Jae Seung; Kim, Tae Ho; Kong, In Deok (Scientific reports, 2020)
Insulin resistance is associated with increased risk for and recurrence of breast cancer. Recently, Wnt1-inducible signaling pathway protein-1 (WISP-1) was reported to impair glucose metabolism and insulin sensitivity. In various cancer tissues, Wnt signaling is upregulated and induces further oncogenic and metastatic activity. However, the effects of exercise on serum levels of WISP-1 and its upstream β-catenin have not been studied in cancer patients. We investigated the effects of exercise training on Wnt signaling and insulin sensitivity in breast cancer survivors (BCS). This single-center trial randomized 46 BCS into either 12-week exercise or control groups (1:1), and included an additional 12 age-matched healthy women. Kinanthropometric parameters, serum Wnt signaling markers, and gluco-lipid profiles were evaluated before and after the intervention. Serum β-catenin and WISP-1 concentrations were significantly higher in BCS than in healthy subjects. There was a positive correlation between β-catenin and WISP-1 levels. Exercise training in BCS significantly reduced body fat and waist circumference and enhanced aerobic and muscular fitness. Exercise decreased β-catenin and WISP-1 levels and improved gluco-lipid profiles. There was a notable correlation between changes in HOMA-IR indexes and serum WISP-1, but not with β-catenin during the exercise intervention. In conclusion, a 12-week community-based exercise intervention resulted in significant reductions in serum β-catenin and WISP-1 levels, accompanied by favorable improvements in body composition, physical fitness, and biochemical parameters in BCS. We also highlight that this is the first report concerning effects of exercise on circulating β-catenin and WISP-1 levels and correlations between WISP-1 and insulin sensitivity, which could be important for determining prognoses for BCS.